Intraspecific variation in the cranial osteology of Diplometopon zarudnyi (Squamata: Amphisbaenia: Trogonophidae). (5th September 2022) - Hawkins, Rebecca K.; Bell, Christopher J.; Olori, Jennifer C.; Stocker, Michelle R.
Abstract: A snake‐like body plan and burrowing lifestyle characterize numerous vertebrate groups as a result of convergent evolution. One such group is the amphisbaenians, a clade of limbless, fossorial lizards that exhibit head‐first burrowing behavior. Correlated with this behavior, amphisbaenian skulls are more rigid and coossified than those of nonburrowing lizards. However, due to their lifestyle, there are many gaps in our understanding of amphisbaenian anatomy, including how their cranial osteology varies among individuals of the same species and what that reveals about constraints on the skull morphology of head‐first burrowing taxa. We investigated intraspecific variation in the cranial osteology of amphisbaenians using seven individuals of the trogonophid Diplometopon zarudnyi . Variation in both skull and individual skull element morphology was examined qualitatively and quantitatively through three‐dimensional (3D) models created from microcomputed tomography data. Qualitative examination revealed differences in the number and position of foramina, the interdigitation between the frontals and parietal, and the extent of coossification among the occipital complex, fused basioccipital and parabasisphenoid ("parabasisphenoid‐basioccipital complex"), and elements X. We performed 3D landmark‐based geometric morphometrics for the quantitative assessment, revealing shape differences in the skull, premaxilla, maxilla, frontal, and parietal. The observed intraspecific variation may be the result of different stages of ontogenetic development or biomechanical optimization for head‐first burrowing. For example, variation in the coossification of the occipital region suggests a potential ontogenetic coossification sequence. Examination of these areas of variation across other head‐first burrowing taxa will help determine if the variation is clade‐specific or part of a broader macroevolutionary pattern of head‐first burrowing. Abstract : Skulls of the amphisbaenian Diplometopon zarudnyi were found to have intraspecific variation in the angle of their rostrum, pattern of frontal‐parietal interdigitation, coossification of the occipital region, shape of individual skull elements, and shape, number, and placement of foramina. We also report a potential postnatal ontogenetic coossification sequence and a new fusion state for the occipital region. This variation may be tied to ontogeny or burrowing biomechanics. Research Highlights: Skulls of the amphisbaenian Diplometopon zarudnyi were found to have intraspecific variation in foramina, interdigitation, coossification, rostrum angle, and skull element shape. This variation may be tied to ontogeny or burrowing biomechanics.